2016
DOI: 10.3109/09540261.2016.1160878
|View full text |Cite
|
Sign up to set email alerts
|

Yoga and physical exercise – a review and comparison

Abstract: Yoga is a multifaceted spiritual tool with enhanced health and well-being as one of its positive effects. The components of yoga which are very commonly applied for health benefits are asanas (physical postures), pranayama (regulated breathing) and meditation. In the context of asanas, yoga resembles more of a physical exercise, which may lead to the perception that yoga is another kind of physical exercise. This article aims at exploring the commonalities and differences between yoga and physical exercise in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(92 citation statements)
references
References 56 publications
1
86
0
5
Order By: Relevance
“…Yogic practice is considered superior to traditional exercise as results obtained after highintensity workouts are quantitative at the muscular level when compared with the qualitative output of yoga practice that leads to the energization of the chakras (body energy centers) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Yogic practice is considered superior to traditional exercise as results obtained after highintensity workouts are quantitative at the muscular level when compared with the qualitative output of yoga practice that leads to the energization of the chakras (body energy centers) [27].…”
Section: Discussionmentioning
confidence: 99%
“…A review and comparison between yoga and physical exercise were conducted by Govindaraj et al , which concluded that yoga interventions are equal and/or superior to physical exercises in most outcomes. [6]…”
Section: Discussionmentioning
confidence: 99%
“…Yoga exercise is composed of physical (asana), breathing (pranayama), and mental (pratyahara) practices, resulting in health, relaxation, and positive awareness. [6] Yoga is now recommended as a noninvasive method and easily accessed intervention for pain relief that is safe and cost-effective with minimal or no side effects. Moreover, regular practice of yoga has positive effects onthe menstrual cycle and psychobiological well-being probably by balancing the neuroendocrinal axis.…”
Section: Introductionmentioning
confidence: 99%
“…Further with its multidimensional and holistic focus on the physical, mental and spiritual approach, yoga may be more suitable and manageable than normal exercise for elderly [44]. Further yoga emphasized on breath regulation, mindfulness and maintenance of postures, which is not a part of normal exercises [45]. Studies previously conducted, compared the effect of yoga on non-active controls [46].…”
Section: Rationalementioning
confidence: 99%